How does atropine exert its anti‐myopia effects?. (12th May 2013) - McBrien, Neville A.; Stell, William K.; Carr, Brittany
<x xml:space="preserve">Abstract</x> In the following point‐counterpoint article, internationally‐acclaimed myopia researchers were challenged to defend the two opposing sides of the topic defined by the title; their contributions, which appear in the order, Point followed by Counterpoint, were peer‐reviewed by both the editorial team and an external reviewer. Independently of the invited authors, the named member of the editorial team provided an Introduction and Summary, both of which were reviewed by the other members of the editorial team. By their nature, views expressed in each section of the Point‐Counterpoint article are those of the author concerned and may not reflect the views of all of the authors.